Intrapulmonary pharmacokinetics of cefiderocol, a novel siderophore cephalosporin, in healthy adult subjects - Katsube, Takayuki (J Antimicrob Chemother, 2019)
BACKGROUND: Cefiderocol, a novel siderophore cephalosporin, has shown potent activity against Gram-negative bacteria, including MDR pathogens. Cefiderocol is under clinical investigation for the treatment of serious Gram-negative infections including nosocomial pneumonia. OBJECTIVES: This study assessed intrapulmonary penetration after a single intravenous dose of cefiderocol (2000 mg infused over 60 min) in healthy adult males. MATERIALS AND METHODS: Each subject underwent one bronchoscopy with bronchoalveolar lavage (BAL) to collect BAL fluid (BALF). Fifteen subjects were assigned to one of three collection timepoints (1, 2 or 4 h from start of infusion). Five additional subjects were assigned to a collection timepoint at 6 h, which was added based on concentration data between 1 and 4 h predicting measurable BALF cefiderocol concentrations at 6 h. RESULTS: Cefiderocol concentrations in plasma, epithelial lining fluid (ELF) and alveolar macrophages (AMs) were calculated for each subject. The ELF concentration of cefiderocol was 13.8, 6.69, 2.78 and 1.38 mg/L at 1, 2, 4 and 6 h after single intravenous dosing, respectively. Over 6 h, geometric mean concentration ratios ranged from 0.0927 to 0.116 for ELF to total plasma and from 0.00496 to 0.104 for AMs to total plasma. AUC ratios of ELF and AMs to plasma were 0.101 and 0.0177 based on total drug in plasma, respectively, and 0.239 and 0.0419 based on free drug in plasma, respectively. There were no major drug-related adverse events. CONCLUSIONS: Results of this study indicate that cefiderocol penetrates into ELF, and ELF and plasma concentrations appear to be parallel.